Politeness Strategies Used By the Characters in the Help Subtitle: A Sociolinguistic Study - Adella Noor Fajrin Hidayatulloh (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Politeness strategies are the strategies used by individuals to maintain face and minimize FTA. Politeness strategies are divided into 4 types, bald on-record, positive politeness, negative politeness, and off-record strategies. The application of politeness strategies is affected by several social factors namely social distance, relative power, and ranking of imposition. This research examines the use of politeness strategies by black maids (BM) and white employers (WE) in The Help movie. The aim of this research is to seek answers for the two research questions: (i) what politeness strategies are used by the characters in The Help movie, and (ii) how do the social distance, relative power and ranking of imposition affect the selection of politeness strategies by the characters. Politeness strategies theory proposed by Brown and Levinson in 1987 is applied as the base theory to conduct the research. This research is conducted using qualitative research methodology because it is based on the use of descriptive data. The source of the data is subtitle of The Help movie which can be accessed from https://www.hotstar.com/id/movies/thehelp/1260071707. The data are the utterances spoken by BM namely Aibileen Clark, Minny Jackson, and Yule May and WE namely Eugenia Phelan (Skeeter), Hilly Holbrook, Celia Foote, Elizabeth Leefolt, and Charlotte Phelan that apply politeness strategies. The utterances considered as data are selected from conversation between WE-WE, WE-BM, BM-WE, and BM-BM. There are 21 data found in total which then were analyzed and classified into four categories based on Brown and Levinson (1987) theory. Then the social distance (D), relative power (P) and ranking of imposition (R) are analyzed to find out how these social factors influence the use of politeness strategies by BM and WE. This research finds that there are 21 utterances spoken by the characters that apply politeness strategies. From the total 21 utterances, there are 2 bald on-record strategies, 8 positive politeness strategies, 8 negative politeness strategies, and 3 off-record strategies. The dominant strategies used by the characters are positive politeness and negative politeness strategies. This research also finds how the D, P, and R affect the selection of politeness strategy by BM and WE. Firstly, the interaction among WE-WE as speaker (S) and hearer (H) shows that the D, P, and R are close and low. Their interaction results in negative politeness as the most dominant strategy. This result is contradictory to Brown and Levinson’s theory which states that negative politeness is going up to superior (Brown & Levinson, 1987: 250). The interaction among WE-BM in which WE performs as S and BM as H shows that the D, P, and R are distant and high. Their interaction results in positive politeness as the most dominant strategy. This result is corresponding to Brown and Levinson’s theory which states that positive politeness is going up inferior (Brown & Levinson, 1987: 250). The interaction among BM-WE in which BM performs as S and WE as H also shows that the D and P are distant and high. However, the R is balanced between high and low, with 2 utterances occur in low R condition and the other 2 in high R condition. Their interaction results in offrecord as the most dominant strategy. This result is in line with Brown and Levinson’s (1987: 78) theory which states that ‘one goes off-record where an imposition is small but relative S-H distance and H’s power are great. Lastly, the interaction among BM-BM as S and H shows that the D, P, and R are close and low. Their interaction results in positive politeness as the most dominant strategy.
Reupload File Repositori 11 Februari 2026_Rudy K/Lia
Keywords: Politeness Strategies; Characters; Subtitle